Metabolic demands of intense aerobic interval training in competitive cyclists - Stepto, N. K.; Martin, D. T.; Fallon, K. E.; Hawley, J. A. (Medicine & Science in Sports & Exercise, 2001)
Purpose: To investigate the metabolic demands of a single session of intense aerobic interval training in highly trained competitive endurance cyclists. Methods: Seven cyclists (peak O2 uptake [O2peak] 5.14 +/- 0.23 L.min-1, mean +/-SD) performed 8 x 5 min work bouts at 86 +/- 2% of O2peak with 60-s recovery. Muscle biopsies were taken from the vastus lateralis immediately before and after the training session, whereas pulmonary gas exchange and venous blood were sampled at regular intervals throughout exercise. Results: Muscle glycogen concentration decreased from 501 +/- 91 to 243 +/- 51 mmol.kg-1 dry mass (P < 0.01). High rates of total carbohydrate oxidation were maintained throughout exercise (340 ?mol.kg-1.min-1), whereas fat oxidation increased from 16 +/- 8 during the first to 25 +/- 13 ?mol.kg-1.min-1 during the seventh work bout (P < 0.05). Blood lactate concentration remained between 5 and 6 mM throughout exercise, whereas muscle lactate increased from 6 +/- 1 at rest to 32 +/- 12 mmol.kg-1 d.m. immediately after the training session (P < 0.01). Although muscle pH decreased from 7.09 +/- 0.06 at rest to 7.01 +/- 0.03 at the end of the session (P < 0.01), blood pH was similar after the first and seventh work bouts (7.34). Arterial oxygen saturation (%SPO2) fell to 95.6 +/- 1% during the first work bout and remained at 94% throughout exercise: the 60-s rest intervals were adequate to restore %SPO2 to 97%. Conclusion: Highly trained cyclists are able to sustain high steady state aerobic power outputs that are associated with high rates of glycogenolysis and total energy expenditure similar to those experienced during a 60-min competitive ride.